Using sUAS-Acquired Imagery to Map Landslide Susceptibility along the Lake Michigan Shoreline of Wisconsin - Bojdak-Yates, Itai; Marsh, Elliott; McCormick, Cal; Scott, Tyler (Proceedings of the Wisconsin Space Conference, 2022)
Bluffs along the Wisconsin shoreline of Lake Michigan frequently collapse, and this collapse often occurs due to saturation and weakness in a sand layer present in the bluffs. We used an sUAS to collect visible and thermal imagery of bluffs along Lake Michigan in Kewaunee County, WI. We then proceeded to classify this imagery in ArcGIS Pro to determine whether the program’s classification tools could locate the sand layer. Furthermore, we examined imagery before and after a major storm to determine the storm’s effect on water content in the sand layer. Our results indicate that we can use automated computer programs to classify the sand layer based on a combination of visible and thermal imagery. Additionally, we found that large summer storms do not significantly alter the saturation of the sand layer and infer that their effect on bluff collapse is minimal.